Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Air Minum dalam Kemasan (AMDK) Ades di Wilayah Rungkut Surabaya - Ian Pandya Putra Pratama; Hery Pudjoprastyono (Universitas Batanghari, 2023)
This study aims to determine the effect of brand image and product quality on purchasing decisions of Ades bottled drinking water (AMDK) in the Rungkut area of Surabaya. In carrying out this research using quantitative studies. To determine the sample using non-probability sampling method using purposive sampling technique, a sample of 100 people from the Rungkut area of Surabaya. The data collection method is through a questionnaire distributed to residents of the Rungkut area, Surabaya. The variables used in this study are independent variables, namely brand image (X1), product quality (X2), and the dependent variable is purchase decision (Y). This analysis technique uses the partial least squares (PLS) model to test the relationship formed between one or more independent variables and one or more dependent variables. The results show that the better the brand image and product quality, the better the decision to purchase bottled drinking water ) Ades in the Rungkut area of Surabaya.